Hemosiderotic dermatofibroma: clinical and dermoscopic presentation mimicking melanoma - Laureano, André (J Dermatol Case Rep, 2015)
BACKGROUND: Dermatofibromas are common benign skin neoplasms. MAIN OBSERVATIONS: The authors report the clinical, dermoscopic and histopathological features of a hemosiderotic dermatofibroma mimicking melanoma in an 85-year-old woman. CONCLUSIONS: Atypical dermoscopic patterns may prove difficult to differentiate from melanocytic lesions, and because of its polymorphic, melanoma-like presentation, definite diagnosis of hemosiderotic dermatofibroma can be reached by histopathological examination.